Amount and type of everyday technology use over time in older adults with cognitive impairment. (May 2014) - Hedman, Annicka; Nygård, Louise; Almkvist, Ove; Kottorp, Anders
Abstract Objectives: This two-year study examined everyday technology (ET) use in older adults with mild cognitive impairment (MCI) testing five predefined theoretical assumptions regarding factors potentially influencing the amount of ET used in everyday life. Methods: Data from 37 participants with MCI were collected at inclusion, six, 12, and 24 months, on the type and amount of ET used and how difficult this was, activity involvement, and cognitive and diagnostic status. These variables were, together with age group (55–64, 65–74, or 75–84 years) and educational level, analysed in a mixed-linear-effect model. Results: A significant decrease in the overall amount of ET used was found over time, but the number of users of specific ETs both decreased and increased. Increasing perceived difficulty in ET use, less activity involvement, decreasing cognitive status, and belonging to the oldest age group significantly decreased ET use. Two years after inclusion 42% of the participants had converted to dementia, but neither change in diagnostic status nor length of education contributed significantly to the predictive model. Conclusion: Over time, a decreasing use of ET was shown in this sample with MCI. This process was influenced by several aspects important to consider in occupational therapy intervention planning.